2015
DOI: 10.1002/wsbm.1292
|View full text |Cite
|
Sign up to set email alerts
|

A practical model for economic evaluation of tissue‐engineered therapies

Abstract: The authors have declared no conflicts of interest for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Specifically, it has been estimated that endothelial cells from a pair of donor corneas may, after 2 in vitro passages over 6 weeks, generate sufficient progeny cells to create at least 90 TE-EK constructs. 19 At present, intracameral free-cell suspension has been demonstrated, in the setting of an open-label clinical trial, to effectively treat corneal endothelial decompensation secondary to various conditions including FECD, cataract surgery, argon laser peripheral iridotomy (LPI), and pseudoexfoliation syndrome. 2 The same study, however, also found a relatively large range of CEC densities among recipients of cell injection therapy, 2 years after treatment.…”
Section: Current State Of Art Cell Augmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it has been estimated that endothelial cells from a pair of donor corneas may, after 2 in vitro passages over 6 weeks, generate sufficient progeny cells to create at least 90 TE-EK constructs. 19 At present, intracameral free-cell suspension has been demonstrated, in the setting of an open-label clinical trial, to effectively treat corneal endothelial decompensation secondary to various conditions including FECD, cataract surgery, argon laser peripheral iridotomy (LPI), and pseudoexfoliation syndrome. 2 The same study, however, also found a relatively large range of CEC densities among recipients of cell injection therapy, 2 years after treatment.…”
Section: Current State Of Art Cell Augmentationmentioning
confidence: 99%
“…Specifically, it has been estimated that endothelial cells from a pair of donor corneas may, after 2 in vitro passages over 6 weeks, generate sufficient progeny cells to create at least 90 TE-EK constructs. 19…”
Section: Current State Of Artmentioning
confidence: 99%
“…QALY analysis for cell-based therapies currently serves as a key stratagem in cost effectiveness evaluations, forming a basis for interventional approval, treatment discontinuation and reimbursement mechanisms [44,45]. For example, bio-engineered skin substitutes utilised by plastic and reconstructive surgeons have been shown to successfully demonstrate gains in cost per QALY [46] whereas Sipuleucel-T (Provenge), a cell based therapy used by onco-urologists, has been withdrawn from the EU following a cost-effectiveness analysis by the NICE Appraisal Committee. The calculation of between £61204 and £108585 per QALY fell well outside the usual cost-effectiveness threshold and Sipuleucel-T was consequently not recommended for adoption [44].…”
Section: Contextual or Condition Specific Considerationsmentioning
confidence: 99%